Elemental composition and radical formation potency of PM10 at an urban background station in Germany in relation to origin of air masses. (March 2015) - Hellack, Bryan; Quass, Ulrich; Beuck, Henning; Wick, Gabriele; Kuttler, Wilhelm; Schins, Roel P.F.; Kuhlbusch, Thomas A.J.
Abstract: At an urban background station in Mülheim-Styrum, North Rhine Westphalia, Germany, a set of 75 PM10 samples was collected over a one year period, followed by analyses for mass, chemical composition and hydroxyl radical (OH) formation potency. Additionally, the origin of air masses for the sampling days was calculated by 48-h backward trajectories, subdivided into the four cardinal sectors. Significant lower PM10 mass concentrations were observed for summertime air masses from the west compared to the other seasons and cardinal sectors. For the OH formation potency higher values were detected if air masses originate from east and south, thus predominantly being of continental origin. From the elevated OH formation potencies in fall and winter a seasonal trend with low potencies in summers is assumed. Furthermore, source apportionment was performed by a positive matrix factor analysis, separating seven plausible factors which could be attributed to mineral dust, secondary nitrate, industry, non-exhaust traffic, fossil fuel combustion, marine aerosol and secondary aerosol factors. The intrinsic OH formation potency was found to be associated mainly with the fossil fuel combustion factor (45%) and industry factor (22%). Highlights: PM10 radical formation potency is correlated to sources and origin of air mass. Source apportionment for the PM10 radical formation potency was performed. The PM10 radical formation potency was linked to the fossil fuel combustion factor. A seasonal trend for the PM10 radical formation potency was observed.